2005
DOI: 10.1590/s0034-89102005000500003
|View full text |Cite
|
Sign up to set email alerts
|

Intra-familial physical violence among Mexican and Egyptian youth

Abstract: ObjectiveTo determine the prevalence of experiencing intra-familial violence among Mexican and Egyptian youth and to describe its associated risk factors. Methods Data from questionnaires applied to 12,862 Mexican and 5,662 Egyptian youth, aged 10 to 19, who attended public schools were analyzed. Biviarate and logistic regression analysis were used to determine the relationship between socio-demographics, the experience of intra-familial violence and violence perpetration. ResultsThe prevalence of having exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…The proportion of youths reporting any form of interpersonal violence was comparable to that found in research with urban middle school students—60% versus 59%, respectively (Ramos-Lira et al 2006). Rates of family violence (involving parents or other members) were particularly high—47% in this sample versus 14% in another central Mexican youth sample (Rivera-Rivera et al 2005). Rates of physical fighting were also higher in this sample—25% as compared to 19% in another youth sample (Rivera-Rivera et al 2005).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The proportion of youths reporting any form of interpersonal violence was comparable to that found in research with urban middle school students—60% versus 59%, respectively (Ramos-Lira et al 2006). Rates of family violence (involving parents or other members) were particularly high—47% in this sample versus 14% in another central Mexican youth sample (Rivera-Rivera et al 2005). Rates of physical fighting were also higher in this sample—25% as compared to 19% in another youth sample (Rivera-Rivera et al 2005).…”
Section: Discussionmentioning
confidence: 56%
“…An additional line of research focuses on violence among students who are part of the traditional school system (e.g., Instituto Nacional de Salud Pública 2009; Ramos-Lira et al 2006). A study of 12,862 public school students, aged 10–19 years, in the central Mexican city of Morelos found that 14% had experienced physical violence at the hands of a family member (Rivera-Rivera et al 2005). Boys relative to girls and urban youths relative to rural youths were more likely to have experienced this violence.…”
Section: Introductionmentioning
confidence: 99%
“…Half of delinquent girls participated in the current study experienced different forms of abuse (physically, emotionally, or sexually) at home. Harmoniously, having experienced intra-familial violence Egyptian females were at slightly greater risk than their male counterparts (Rivera-Rivera et al, 2005). Females who engage in antisocial or delinquent juvenile behavior are more likely to have histories of abuse and victimization within the family environment (Grande et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Desta forma, os óbitos por causas violentas entre a faixa etária mais jovem, de baixas condições socioeconômicas e com níveis de escolaridade baixos, são relatados por muitos autores como uma complexa rede de fatores que envolvem as mortes por causas externas (52,54) . Especificamente em relação aos acidentes, o comportamento da família, o estilo de vida, a supervisão inadequada sobre a criança, os fatores educacionais, econômicos, sociais e culturais, além das características relativas à criança (fase de desenvolvimento, curiosidade e comportamento) e as condições do ambiente, guardam relação direta com os eventos não intencionais (55) .…”
Section: Fatores Multicausaisunclassified